Spectral analysis of gas-dynamic characteristics of pulsing gas flows in the exhaust system of a piston engine - L. V. Plotnikov; Yu. M. Brodov; B. P. Zhilkin; L. E. Osipov; K. O. Desyatov (Известия высших учебных заведений: Проблемы энергетики, 2022)
THE PURPOSE. To On the basis of spectral analysis, to evaluate the effect of installing a turbocharger turbine on the aeromechanics of pulsating gas flows in the engine exhaust system and to propose a method for controlling the aerodynamic and heat transfer characteristics of unsteady gas flows by creating an ejection effect in the exhaust system.METHODS. A laboratory experiment on a full-scale piston engine model was chosen to achieve this goal. Spectral analysis of harmonic dependences was used to assess changes in the structure of gas flows in the exhaust system. Mathematical modeling of the operating cycle of diesel engines was used to assess the potential positive effects of the use of an ejection system in the exhaust tract of a diesel engine. Three-dimensional solid modeling systems were used for sketch (engineering) studies of new (modernized) exhaust system designs.RESULTS. The article describes laboratory equipment, measuring system and data processing methods. A description of the boundary conditions in the course of experimental research is given. Comparison of aeromechanical and heat exchange characteristics of unsteady flows in the exhaust system of an engine with and without a turbocharger is carried out in the article. The qualitative and quantitative differences in aeromechanics and thermal physics of processes are shown. The proposed method of aeromechanical improvement of the exhaust system by creating an ejection.CONCLUSION. It was revealed that the turbine of a turbocharger has a significant effect on the aeromechanical characteristics of flows in the exhaust system. A significant decrease in the maximum flow rate in the exhaust tract (up to 3 times) is observed when installing a turbocharger. There is a decrease in flow characteristics through the turbocharged exhaust system (within 30%). It was found that the ejection effect in the engine exhaust system leads to stabilization of the flow, an increase in gas consumption by 6-12%, a decrease in specific fuel consumption by an average of 1% and an improvement in reliability indicators by 1.11-1.74%.